Diagnostic criteria for idiopathic inflammatory myopathies. Problems of their optimization - O. A. Antelava; S. G. Radenska-Lopovok; E. L. Nasonov (Современная ревматология)
The paper deals with the problems of optimizing the diagnostic criteria for idiopathic inflammatory myopathies (IIM), a group of heterogeneous rare autoimmune diseases characterized by inflammatory lesion in the skeletal muscles. The representatives of this group are traditionally considered to be polymyositis (PM), dermatomyositis (DM), and inclusion-body myositis. The authors detail the history of classification criteria for IIM from those proposed by T.A. Medsger et al. (1970) relying on its clinical picture, laboratory data and instrumental findings, as well as the criteria (including the first introduced exclusion ones) elaborated by A. Bohan and J.B. Peter in 1975, which remain fundamental in both clinical practice and researches. The basis for the clinical and serological criteria proposed by Y. Troyanov et al. (2005) for IIM is the identification of myositis-overlap syndromes. The classificational (subtype identification) and therapeutic value of the criteria based on clinical and serological characteristics was supported by the Hungarian investigators A. Vancsa et al. (2010) who investigated the relationship between the clinical and therapeutic characteristics of IIM and positivity for myositis-specific and myositis-associated antibodies. The criteria developed by M.C. Dalakas (1991, 2003) are based on the specific immunopathological features of a histological pattern, which allow the differentiation of DM, PM, and inclusion-body myositis from other myopathic syndromes. The 2004 European Neuromuscular Center (ENMC) criteria first identify necrotizing autoimmune myopathy and nonspecific myositis as individual subtypes. The serological classification of IIM, which is based onthe assessment of autoantibodies that play an important role in the pathogenesis of the disease, is of indubitable interest. There is an obvious need for the correct and timely diagnosis of both IIM as a whole and its subtypes in particular, which is complicated by theheterogeneity of the latter. The proposed approaches to diagnosing and classifying IIM have their advantages and disadvantages so that work in this direction is yet to be under way.